Diagnostic Accuracy of Blood-Based Biomarkers for Early Detection of Alzheimer’s Disease: A Systematic Review - Cindy Permata Sari; Rocksy Fransiska V. Situmeang; Tandry Meriyanti (Universitas Pelita Harapan, 2026)
Introduction: Alzheimer’s disease (AD) continues to impose a significant global health burden, while early detection remains limited by the reliance on invasive and costly diagnostic methods such as PET imaging and cerebrospinal fluid (CSF) analysis. Blood-based biomarkers have gained attention as a more accessible alternative. This study aims to assess the diagnostic performance of plasma p-tau217, p-tau181, and Aβ42/40 in detecting early-stage AD. Methods: A systematic review was conducted using predefined inclusion criteria. Studies were selected if they evaluated plasma biomarkers against established reference standards (CSF biomarkers, PET imaging, or neuropathology), reported diagnostic accuracy measures, and included individuals with early cognitive impairment. Extracted data covered study characteristics, assay methods, population profiles, cutoff approaches, and longitudinal outcomes. Results: Seventeen studies involving more than 7,000 participants were included. Plasma p-tau217 consistently demonstrated the highest diagnostic accuracy across studies, with AUC values generally exceeding 0.90. Plasma p-tau181 also showed good diagnostic performance but with greater variability, particularly in early disease stages. In contrast, Aβ42/40 alone exhibited lower and less consistent accuracy, although its performance improved when combined with phosphorylated tau biomarkers. Variability in assay platforms, population characteristics, and cutoff values contributed to heterogeneity across studies. Conclusions: Plasma p-tau217 shows strong and consistent diagnostic performance across different populations and settings, approaching that of CSF and PET biomarkers. It holds considerable potential as a practical and minimally invasive tool for early AD detection, although further standardization is still needed. Keywords: Alzheimer’s Disease, P-tau217, Blood-based Biomarkers, Early Detection, Diagnostic Accuracy